Development and characterization of expressed sequence tag -simple sequence repeat markers from kelampayan tree transcriptome (NCDBEST) - Lai, Pei Sing (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Neolamarckia cadamba (Roxb.) Bosser (Kelampayan) is a fast-growing timber species that plays an important role in plywood and furniture production industries which brings huge exportation income to Malaysia. Thus, the development of expressed sequence tag-simple sequence repeat (EST-SSR) markers for Kelampayan is essential to provide an environmentally sustainable resource that yield quality woods and increase the production simultaneously. These markers help in the selection of seedlings with desired traits in order to meet the requirement for producing high quality wood products. In this study, two mother trees were selected and 25 seedlings from each mother tree were collected for polymorphism assessment. The protocol for ‘Touch-n-Go’ (aka fasTiP-X kit) approach was developed in this study and Flinders Technology Associates (FTA®) technology was successfully optimized in preparing Kelampayan DNA for Polymerase Chain Reaction (PCR). The fasTiP-X kit appeared to be less time and cost consuming method whereas FTA® technology was found to be superior in storage. This indicates fasTiP-X kit appears to be the most suitable method for high-throughput genotyping and therefore it was used for DNA extraction in this study. A total of 155 (2.34%) EST sequences were successfully extracted from NcdbEST and it contained 232 SSRs. From the EST-SSR sequences, 60 (38.70%) ESTs contained more than one SSR while the remaining (61.29%) contained only one SSR. Analysis of SSR motifs revealed that the proportion of SSR unit size was not evenly distributed. Furthermore, with the exception of mononucleotide repeats, the dominant repeat motif found were tri-nucleotide repeats (61.20%), di-nucleotide repeats (27.16%), tetra-nucleotide repeats (7.33%), hexa-nucleotide repeats (3.02%) and pentanucleotide repeats (1.29%). Besides, eight perfect compound repeats were detected and nine SSRs which were separated by less than six nucleotides were categorized as imperfect compound repeats. A total of 24 EST-SSR markers were designed according to the criteria but only 18 which consist of 86 alleles were used throughout this study. The number of alleles ranged from 1 to 10 with average of 4.17 and 4.11 alleles per locus for mother tree 1 and 2, respectively. The observed heterozygosity was ranged from 0 to 1 with mean value of 0.222 ± 0.309 and 0.231 ± 0.322 for mother trees 1 and 2, respectively. The highest polymorphism information content (PIC) value was 0.857 and 0.876 for each mother tree, respectively. In parentage assignment analysis, 54.8% and 40.2% of alleles detected were probably originated from mother trees 1 and 2, respectively. However, both mother trees were found to be genetically distantly related with their progenies. This indicates that the mating system of Kelampayan has high probability to be predominantly outcrossed. Three loci were found to be transferable to all the cross-genera species and 10 out of 18 EST-SSR markers used were transferable to more than four cross-genera species. Kelampayan has high posibility to be genetically closer to Gardenia jasminoides due to the highest transfer rate (94.74%). The EST-SSR markers developed in this study could be applied in plant breeding and improvement programme as well as conservation of plant genetic resources either for Kelampayan or other Rubiaceaes due to its transferability property in future.